(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s and the world’s ophthalmic pharmaceutical markets are both expanding and growing. This review article provides an overview of the current pharmaceutical market globally and contrasts the situation in India with the international ophthalmic drug markets. It also provides additional insights into the relative growth and contribution of each individual ophthalmic therapy segment as well as a look at the pipeline for ophthalmic drugs in the future.